2020
DOI: 10.4252/wjsc.v12.i4.266
|View full text |Cite
|
Sign up to set email alerts
|

Insights of stem cell-based endogenous repair of intervertebral disc degeneration

Abstract: Low back pain has become more prevalent in recent years, causing enormous economic burden for society and government. Common therapies used in clinics including conservative treatment and surgery can only relieve pain. Subsequent cell-based treatment such as mesenchymal stem cell transplantation poses problems such as short duration of therapeutic effect and tumorigenesis. Recently, the discovery and identification of stem cell niche and stem/progenitor cells in intervertebral disc bring increased attention to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 69 publications
0
25
0
Order By: Relevance
“… 4 In addition, previous studies showed that stem cells in the adjacent vertebral body could migrate to the NP physiologically through the nutrition channel to maintain the IVD environment balance. 5 , 6 In IVDD, CEP degeneration leads to blockage of the nutrition channel in the endplate, which results in degeneration of the NP and endogenous repair failure. 7 , 8 Therefore, finding an effective method to alleviate CEP degeneration to prevent or reverse IVDD is necessary.…”
Section: Introductionmentioning
confidence: 99%
“… 4 In addition, previous studies showed that stem cells in the adjacent vertebral body could migrate to the NP physiologically through the nutrition channel to maintain the IVD environment balance. 5 , 6 In IVDD, CEP degeneration leads to blockage of the nutrition channel in the endplate, which results in degeneration of the NP and endogenous repair failure. 7 , 8 Therefore, finding an effective method to alleviate CEP degeneration to prevent or reverse IVDD is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, studies on the role of chitosan in cartilage repair are also gradually being carried out (Rusu et al, 2019;George;Tandon and Kandasubramanian, 2020). NP cells are the main components of NP, belonging to the chondroid cells, which can secrete aggrecan and type-II collagen to synthesize extracellular matrix and then maintain the stability of NP (Liu et al, 2020). Theoretically, the gel made of chitosan is also suitable for the nucleus pulposus scaffold of the IVD nucleus pulposus cells.…”
Section: Discussionmentioning
confidence: 99%
“…The declining number of cells, their phenotype modification and the inability to withhold compression stresses lead to the deterioration of the AF lamellar architecture and the reduction in ECM synthesis [41,42]. The low metabolic activity of cells and the avascular nature of IVD may explain the inability to self-repair following injury and degeneration [43]. However, recent research has reported the presence of progenitor stem cells in the NP, which may be physiologically responsible, to a certain extent, for endogenous repair of intrinsic insults to IVD integrity.…”
Section: Intervertebral Disc Degenerationmentioning
confidence: 99%